An optimized catch-only assessment method for data poor fisheries. (22nd December 2017) - Zhou, Shijie; Punt, André E; Smith, Anthony D M; Ye, Yimin; Haddon, Malcolm; Dichmont, Cathy M; Smith, David C
Abstract: Catch statistics are perhaps the most commonly collected data and are widely available for many fisheries. However, it is currently difficult to provide scientific advice for management purposes using only catch data. This article presents a catch-only method for stock assessment of data-poor fisheries. It uses time series of catches and two priors, one for the intrinsic population growth rate derived from life history parameters, and another for stock depletion based on catch trends. The method applies an optimization algorithm to search the potential parameter space. All computations are model or equation based rather than using predefined rules. The utility of this method is demonstrated by applying it to 13 stocks in Australia that are assessed using Stock Synthesis—an assessment package that can make use of a variety of data sources. The estimated parameters, including carrying capacity, intrinsic population growth rate, maximum sustainable yield, and depletion from the catch-only method are broadly comparable with those from the full assessments. The circumstances in which the method may perform poorly, such as longer-term changes in productivity and episodic recruitment, are highlighted.